2020
DOI: 10.1111/jeb.13667
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive senescence and parental effects in an indeterminate grower

Abstract: Reproductive senescence is the decrease of reproductive performance with increasing age and can potentially include trans‐generational effects as the offspring produced by old parents might have a lower fitness than those produced by young parents. This negative effect may be caused either by the age of the father, mother or the interaction between the ages of both parents. Using the common woodlouse Armadillidium vulgare, an indeterminate grower, as a biological model, we tested for the existence of a deleter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 64 publications
0
11
1
Order By: Relevance
“…Paternal age, mating history, and their interaction had no effect on the survival, early-life traits, or immunity of offspring in G. holbrooki. These results are in contrast to other studies that have reported an effect of paternal age on offspring earlylife traits in a wide range of taxa (reviewed in Monaghan et al 2020; also see Cooper et al 2020;Depeux et al 2020;Vuarin et al 2021;Travers et al 2021). However, our results align with an earlier study on G. holbrooki which found no paternal effect, but reported a maternal age effect on offspring early-life traits (Vega-Trejo et al 2018).…”
Section: Discussioncontrasting
confidence: 99%
“…Paternal age, mating history, and their interaction had no effect on the survival, early-life traits, or immunity of offspring in G. holbrooki. These results are in contrast to other studies that have reported an effect of paternal age on offspring earlylife traits in a wide range of taxa (reviewed in Monaghan et al 2020; also see Cooper et al 2020;Depeux et al 2020;Vuarin et al 2021;Travers et al 2021). However, our results align with an earlier study on G. holbrooki which found no paternal effect, but reported a maternal age effect on offspring early-life traits (Vega-Trejo et al 2018).…”
Section: Discussioncontrasting
confidence: 99%
“…To our knowledge, the only study that carried on ageing and immune priming did not observe similar results: old mealworm beetles did not display an immune priming protection by contrast to young individuals, probably because of immunosenescent process (Daukste et al., 2012). But in our case, A. vulgare lives up to two years, still reproduce until three years old (Al‐Dabbagh & Block, 1981; Depeux et al., 2020; Pitelka & Paris, 1962; Warburg et al., 1984) and live in moist soil, an environment particularly rich in microbial density and diversity (Ranjard & Richaume, 2001; Torsvik et al., 1990), where the risks of infection are high. According to Best et al.…”
Section: Discussionmentioning
confidence: 77%
“…Compared to dipterian models, these crustaceans have a long lifespan (natural populations display 13% of two‐year‐old individuals; Pitelka & Paris, 1962; Warburg et al., 1984), especially suitable for ageing effects’ study (Depeux et al., 2020; Pitelka & Paris, 1962). Age and gender induce variations in their immune parameters (Depeux et al., 2020; Pigeault et al., 2014; Sicard et al., 2010) and several species harbour the maternally transmitted endosymbiont Wolbachia (Bouchon et al., 1998; Cordaux et al., 2012). In the common woodlouse Armadillidium vulgare , this intracellular bacterium feminizes genotypic males into functional phenotypic females (Martin et al., 1973; Rigaud & Juchault, 1993; Bouchon et al, 2008), but also protects the host against some pathogens (Braquart‐Varnier et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Among indeterminately growing invertebrates, common woodlouse (Armadillidium vulgare) females of older ages also produce a higher number of larger offspring. Yet, the offspring of older female woodlouse have lower fitness, offsetting the increase in maternal fertility arising from the indeterminate growth (Depeux et al, 2020). The current datasets indicate that indeterminate growth itself is not sufficient to escape reproductive senescence.…”
Section: Role Of Indeterminate Growth In Fish Reproductive Senescencementioning
confidence: 70%